Repair mechanism of Yishen Tongluo formula on mouse sperm DNA fragmentation caused by polystyrene microplastics - Chenming Zhang; Zulong Wang; Sicheng Ma; Rubing Chen; Shiqi Wang; Hao Zhang; Zhong Hua; Zixue Sun (Taylor & Francis Group, 2023)
AbstractContext Plastics can break down into millions of microplastic (MPs, < 5 mm) particles in the soil and ocean. These MPs can then affect the function of the reproductive system. There is currently no effective solution to this problem aside from traditional Chinese medicine. We have previously used Yishen Tongluo formula (YSTL) to treat sperm DNA damage caused by some toxic substances.Objective To investigate the mechanism underlying the repair of mouse sperm DNA fragmentation caused by polystyrene microplastics by YSTL.Materials and methods An animal model of polystyrene microplastic (PS-MP)-induced sperm DNA damage was replicated by gavage of SPF ICR (CD1) mice PS-MPs at 1 mg/d and treated with YSTL at 11.89, 23.78 and 47.56 g/kg, respectively, for 60 days. The Sperm DNA fragmentation index (DFI) of each group was detected and compared. The target genes of YSTL identified by transcriptomic and proteomic analyses were validated by qRT-PCR and western blotting.Results The DFI of the PS group (20.66%) was significantly higher than that of the control group (4.23%). The medium and high doses of the YSTL group (12.8% and 11.31%) exhibited a significant repairing effect. The most enriched pathway was PI3K/Akt. TBL1X, SPARC, hnRNP0, Map7D1, Eps8 and Mrpl27 were screened and SPARC was validated.Discussion and conclusions The precise mechanism by which YSTL inhibits PD-MPs DNA damage may be associated with the PI3K/Akt pathway and SPARC. It provides a new direction for using traditional Chinese medicine to prevent and repair reproductive system injury caused by MPs.